New Opportunities in the Diagnosis of Anemia of Chronic Diseases (Eurasian Medical Research Periodical, 2023)
The paper presents its own data on the study of hepcidin content in the blood in iron deficiency anemia and anemia developed in patients with rheumatoid arthritis and bacterial infections. The authors present their own data on the content of hepcidin in practically healthy people. The results of the study indicate an extremely low level of hepcidin in iron deficiency anemia, while in patients with anemia of chronic diseases, the content of hepcidin is significantly high. There were no differences in hepcidin levels in people with AСD with rheumatoid arthritis and bacterial infections of various localization. The study of hepcidin levels in blood serum can be used in the algorithm of differential diagnosis of iron deficiency anemia and functional iron deficiency